Pengaruh Ukuran Perusahaan dan Intensitas Modal Terhadap Tax Avoidance : Studi Empiris Pada Perusahaan Energy Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Salsabila, Syafina; Febriyanto, Muhammad Ikhsan (Prisani Cendekia, 2026)
This study aims to analyze the effect of firm size and capital intensity on tax avoidance practices among energy sector companies listed on the Indonesia Stock Exchange. Tax avoidance is viewed as a managerial strategy to legally minimize tax burdens through aggressive tax planning. This study adopts a quantitative approach using secondary data obtained from corporate financial statements. Panel data regression analysis is employed to generate more comprehensive and accurate results. The findings reveal that firm size does not have a significant effect on tax avoidance, while capital intensity significantly influences the level of corporate tax avoidance. These results indicate that a company’s asset structure plays a more important role in encouraging tax avoidance practices than the scale of the firm itself. This study is expected to contribute theoretically to the development of taxation literature and provide practical insights for stakeholders in formulating more effective tax policies.